STRATEGI DAN KEBIJAKAN PEMERINTAH DALAM MENANGGULANGI PENGANGGURAN (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2013)
Unemployment is a serious problem faced by Indonesia government. It has direct effect to poverty, crimes and other social and politic problems. There are many factors caused unemployment in Indonesia, besides of the low investment, education also blame as a factor caused increasing unemployment problems. The failure is on education system in order to generate human resource which has ability to employee themselves. The paper addresses government’s effort dealing with unemployment problems in Indonesia. Some strategies and policies is needed in order to enhace investment environment and education system in Indonesia.